2015
DOI: 10.1021/acsami.5b01248
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Bacterial Interaction with Copper Surfaces through Graphene and Hexagonal-Boron Nitride Coatings

Abstract: Understanding biological interaction with graphene and hexagonal-boron nitride (h-BN) membranes has become essential for the incorporation of these unique materials in contact with living organisms. Previous reports show contradictions regarding the bacterial interaction with graphene sheets on metals. Here, we present a comprehensive study of the interaction of bacteria with copper substrates coated with single-layer graphene and h-BN. Our results demonstrate that such graphitic coatings substantially suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 45 publications
7
58
0
Order By: Relevance
“…Single and few-layer graphene coatings on SiO 2 substrates were demonstrated to inhibit the bacterial adhesion [52]. Recently, it has been reported that E. coli cells treated with ZnO nanoparticles showed a strikingly high mortality rate of the cells due to a remarkable reduction in bacterial EPS, demonstrating that EPS can protect bacteria through sequestering nanoparticles [53].…”
Section: Resultsmentioning
confidence: 99%
“…Single and few-layer graphene coatings on SiO 2 substrates were demonstrated to inhibit the bacterial adhesion [52]. Recently, it has been reported that E. coli cells treated with ZnO nanoparticles showed a strikingly high mortality rate of the cells due to a remarkable reduction in bacterial EPS, demonstrating that EPS can protect bacteria through sequestering nanoparticles [53].…”
Section: Resultsmentioning
confidence: 99%
“…From these observations, it can be concluded that BNNTs do not seem to have inherent bactericidal effect, and any antibacterial activity observed was due to the coating. By contrast, according to the research conducted by Parra et al, 79 hexagonal BN could be used to prevent the biocorrosion of copper substrates by Escherichia coli. After 24 hours of incubation with BN coated copper sample, bacteria viability came up to 118%, indicating that not only the BN itself does not seem to have any inherent antibacterial ability, but also that it would prevent harming copper ions to interact with the bacteria deposited on the surface.…”
Section: Antibacterial Propertiesmentioning
confidence: 98%
“…1 Among these ENMs, boron nitride (BN) NMs (also known as "white graphene") 2 with a structure analogous to carbon NMs have been studied for drug delivery, tissue regeneration, and fluorescent-cell imaging. [3][4][5] Hydrophobic BN nanospheres (BNNSs) and highly water-soluble BN powder (BN-800-2) with irregular shapes are two representative forms of BN NMs. BNNSs can be utilized to deliver cytosine-phosphate-guanine oligonucleotides and peptides into lysosomes after cellular uptake; [6][7][8] similarly, BN-800-2 with high surface area and loading capacity also possesses the potential of being a drug-delivery vehicle.…”
Section: Introductionmentioning
confidence: 99%